A comprehensive review of summer mortality syndrome in fish: Causes, climate impact, and mitigation strategies - Shafi, Manal E (Journal of Advanced Veterinary and Animal Research, 2025)
Global warming poses a significant threat to aquatic animals, particularly fish production, because of the rising summer temperatures, leading to issues such as summer mortality syndrome. This issue could impact fish farms, leading to 30%–100% mortality rates and significant financial losses. This study aims to identify the underlying causes of summer mortality syndrome in fish and to evaluate modern mitigation strategies to protect aquaculture systems effectively. Mortality rates of stocked fish ranged between 30% and 70%, with some instances reaching 100%. The reasons behind summer mortality syndrome are complex and multifactorial. Contributing factors include pathogenic agents such as bacteria, viruses, fungi, and parasites, as well as poor management practices and unfavorable environmental conditions. Most types of bacteria that caused mortality rates in many fish species were Aeromonas spp., Flexibacter columnaris, Flavobacterium columnare, Pseudomonas spp., and Enterobacteriaceae, namely Edwardsiella tarda, Yersinia spp., and Streptococcus spp. To mitigate the impact of this syndrome, several protective measures can be implemented. These include applying some nutritional inventions such as herbal additives, essential oils, natural compounds, water management, antibiotics, vaccinations, modern technology, and improved management practices. By addressing these factors comprehensively, the risk of summer mortality syndrome can be significantly reduced. This review provides further evidence regarding the effects of summer mortality syndrome in fish. The main causes of this phenomenon are pathogens and poor management. Nutritional additives and vaccinations were effective ways to mitigate these harmful effects to maintain fish production. Further research is needed to evaluate the long-term effectiveness of these mitigation strategies and to develop guidelines for sustainable fish farming practices under changing climatic conditions. J. Adv. Vet. Anim. Res., 12(3): 890–907, September 2025 http://doi.org/10.5455/javar.2025.l951